Conducting Mixed Methods Research Systematic Methodological Reviews: A Review of Practice and Recommendations. (October 2021) - Howell Smith, Michelle C.; Shanahan Bazis, Pamela
Mixed methods research (MMR) methodologists research the use of MMR by conducting systematic methodological reviews (SMR). Unfortunately, there is little guidance on how to conduct these types of reviews. This MMR-SMR of MMR-SMRs identifies a comprehensive pool of published MMR-SMRs ( n = 80), isolating best practices that will guide future reviews thereby increasing their quality and utility to the field of MMR. We summarize our quantitative codes descriptively and integrate the qualitative themes alongside the relevant quantitative results. We contribute to the field mixed methods research by identifying potential topics for future MMR-SMR, summarizing current practices in writing MMR-SMRs, and providing recommendations to consider when publishing future MMR-SMR.